Vintage analysis of Chinese Baijiu by GC and 1H NMR combined with multivariable analysis. (30th October 2021) - Li, Yicong; Fan, Shuangxi; Li, Anjun; Liu, Guoying; Lu, Wei; Yang, Bo; Wang, Fengxian; Zhang, Xin; Gao, Xiaojuan; Lǚ, Zhiyuan; Su, Ning; Wang, Guanghao; et al.
Highlights: Baijiu vintage analysis was achieved by targeted GC and non-targeted 1 H NMR. Three variable selection methods were used to decrease input variables. PLSR vintage model was optimized to have robust prediction performance. Ten components were found as potential vintage markers for Chinese Baijiu. Abstract: Economical-driven counterfeit and inferior aged Chinese Baijiu has caused serious concern of publicity in China. In this study, a total of 167 authentic Chinese Baijiu samples with different vintages including 3 flavor types were carefully collected. Gas chromatography (GC) was used to determine main volatile components and proton nuclear magnetic resonance ( 1 H NMR) spectroscopy was employed to obtain non-targeted fingerprints of Chinese Baijiu samples. Partial least squares regression (PLSR) models, which were confirmed by internal and external validation, were established for effectively identifying actual storage vintage of Chinese Baijiu with various brands, flavor types. Centering (Ctr), pareto scaling (Par), unit variance scaling (UV) data pretreatment methods, principal components (PCs), and three modified variable selection methods were proposed to successfully optimize the vintage model and effectively extract important vintage characteristic factors. This study demonstrated that NMR and GC combined with multivariate statistical analysis are effective tools for validating vintage authenticity of Chinese Baijiu.